What the West could learn from the East: a reflective analysis. Issue 7 (2nd October 2016) - Zou, Yali; Craig, Cheryl J.; Poimbeauf, Rita P.
Abstract: Drawing on Lugones' ideas of world traveling, Dewey's notion of education as experience, and Greene's vision of seeing small/seeing big, this article inquires into lives lived in an Eastern educational milieu with attention reflectively paid to what educators in the West could learn from those in the East. Rather than focusing on mega narratives largely created by policy-makers and derived from accumulations of theory and/or political decision-making, this practical research in the reflective vein takes a 'big' look at three 'small stories' that emerged in a narrative inquiry we conducted in a Chinese elementary school and imagines their portability to Western educational contexts. Reflective attention is specifically paid to: (1) teaching without words, (2) principal images, and (3) shared responsibility for failure. What these small stories from our narrative inquiry research might disrupt, if introduced to Western educational settings, is especially taken up.